COMPARISON OF THE EFFICACY OF DULOXETINE VERSUS DULOXETINE PLUS ORAL VITAMIN D IN TREATING PERIPHERAL DIABETIC NEUROPATHY - JEHANGIR , HMS; KHAN , S; HUSSAIN, A; KHOKHAR , HS; IQBAL, H; ASIF, S; MAHBOOB , HM (Biological and Clinical Sciences Research Journal, 2022)
Painful diabetic peripheral neuropathy (PDPN) is a common complication of diabetes mellitus that affects the quality of life. Duloxetine and vitamin D have been used for its management, but there is limited literature comparing the efficacy of these drugs. In this study, we aimed to compare Duloxetine alone versus Duloxetine in combination with vitamin D for treating PDPN. An open-labeled randomized controlled trial was conducted at King Edward Medical University, Mayo Hospital, Lahore, for a duration of 6 months, starting from July 1, 2021, to December 31, 2021. The study included 78 patients aged 20 to 60 years suffering from PDPN as per inclusion and exclusion criteria. Participants were randomly assigned to two groups, with 39 participants in each group. Group A was given Duloxetine 60mg OD, and Group B was given Duloxetine 60mg OD plus oral Vitamin D3 2000IU daily for 8 weeks. Patients were assessed before the start of treatment and followed up after 8 weeks in the outpatient department to measure the mean reduction in pain score using the Visual Analogue Scale. All the collected data was analyzed using SPSS 26.0. The mean age of the participants was 44.46 ± 6.51 years. Of the 78 participants, 51 were female, and 27 were male. 89.8% of patients tolerated the drugs well with no side effects. Only 6.4% of patients complained of tiredness, and 3.8% experienced constipation. The mean VAS before treatment and at the end of the 8th week was 7.41 ± 0.98 and 3.48 ± 1.01, respectively. There was a marked reduction in pain after using both regimens, which was statistically significant (p-value < 0.001). The mean VAS before and after the treatment in Group A was 7.46 ± 0.99 and 4.17 ± 0.72, respectively. In Group B, the mean VAS before and after the treatment was 7.35 ± 0.978 and 2.79 ± 0.832, respectively. This reduction was statistically significant compared to the two groups (p-value < 0.001). The combination of Duloxetine and vitamin D proved superior to the Duloxetine group and is a recommended regimen according to our results. Further studies with more extensive data from multiple centers are required to establish the guidelines.